2019
DOI: 10.1099/ijsem.0.004734
|View full text |Cite
|
Sign up to set email alerts
|

Altererythrobacter muriae sp. nov., isolated from hypersaline Añana Salt Valley spring water, a continental thalassohaline-type solar saltern

Abstract: A novel salt-tolerant alpha-proteobacterium, designated SALINAS58T, was isolated from Santa Engracia hypersaline spring water in the Añana Salt Valley, Álava, Spain. The isolate was Gram-negative, aerobic, non-motile, catalase-positive, oxidase-negative, rod-shaped and formed orange colonies on marine agar. Optimal growth was observed at pH 6.0–6.5, at 30 °C and in the presence of 1% (w/v) NaCl. The main cellular fatty acids (>20%) were summed feature 8 (C18 : 1 ω7c and/or C18 : 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…The description is the same as for A. muriae [41]. Genome phylogenomic analysis strongly supported the placement of this species in the genus Pontixanthobacter .…”
Section: Description Of Alteripontixanthobacter Muriaecomb Novmentioning
confidence: 75%
“…The description is the same as for A. muriae [41]. Genome phylogenomic analysis strongly supported the placement of this species in the genus Pontixanthobacter .…”
Section: Description Of Alteripontixanthobacter Muriaecomb Novmentioning
confidence: 75%
“…BLAST analyses (data not shown) of operational phylogenetic units (OPUs), accounting for >1% of the sequences in each sample, indicated that the OPUs were closely related to sequences retrieved from other hypersaline environments worldwide, either terrestrial or aquatic. Very recently, a new species of Alpha‐proteobacteria ( Altererythrobacter muriae ) has been isolated from the SE spring (Muniozguren et al ., 2021). In our dataset this bacterium corresponded to OPU 114 (Supplementary Dataset 1) that was detected, albeit at very low abundance, in HU, as also indicated by recruiting the reads from the four cellular metagenomes generated in this work (data not shown) to A .…”
Section: Metagenomic Analysis Of Cell and Virus Assemblagesmentioning
confidence: 99%
“…As a result of new technologies such as fluorescence in situ hybridization (FISH) and metagenomics, life can now be detected in the most extreme environments. Among these, the study of microorganisms in hypersaline environments such as solar salterns 6 , 7 , saltpans 8 , salt mines 9 , oceans 5 , 10 , and salt lakes 11 16 has received considerable interest. Microorganisms that have adapted to life at high salt concentrations are found in three domains of life: Archaea, Bacteria, and Eukarya 4 , 13 , 17 22 .…”
Section: Introductionmentioning
confidence: 99%